Relationship between head lice (Pediculus humanus capitis) infestation and nutritional status of children (Dhaka University Journal of Biological Sciences, 2014)
The prevalence of head lice (Pediculus humanus capitis) infestation and malnutrition affect among the children (1 to 7 years) in the area of Mirpur Bihari Camp, Dhaka was observed. A total of 300 children were examined during February 2011 to January 2012, and among them 59.67% prevalence of head lice was observed. The height and weight for age was compared following 50th percentile or standard deviation score (SD?score) of WHO/ NCHS reference standard. In case of WAZ (weight for age using Z?score value) of boys, moderate malnutrition was found in 2, 3, and 5 years age group and mild malnutrition was found in 1, 4, 6 and 7 years age group. In case of WHZ (weight for height of boys), mild malnutrition was found in age group 2, 3 and 5 years. In better growth children, 56.67% were infested by head lice, 56% in medium growth children and the highest 65.46% among the children with mild growth. The intensity of infestation was mostly mild and moderate. DOI: http://dx.doi.org/10.3329/dujbs.v23i2.20091 Dhaka Univ. J. Biol. Sci. 23(2): 119-125, 2014